Evaluative Framework CIPP Model for the Tadarub Ala Ad-Dakwah Program at Madrasah Aliyah School - Gusni, Gusni; Mania, Sitti; Rasyid, Muhammad Nur Akbar (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The Ad-Dakwah-style tadarub program at Islamic High School, or Madrasah Aliyah DDI Paria, is an important effort to improve Qur'an literacy and build students' religious character. However, the effectiveness of this program has not been comprehensively evaluated, requiring a comprehensive evaluative framework. This study intends to evaluate the tadarub program using the CIPP (Context, Input, Process, Product) Model, which assesses the program's context, input, process, and product aspects. The research method used was a combined approach with data collection through interviews, observations, document analysis, and questionnaires with participants and program instructors. The evaluation results indicate that the tadarub program is relevant to the needs of participants and the school environment and supported by adequate human resources and facilities despite the limited number of instructors. The implementation process was structured but faced obstacles such as participant absence and time constraints. The program's products showed significant improvements in Qur'an reading skills and basic tajweed understanding, although the results were not evenly distributed across all participants. Based on these findings, recommendations include increasing the number of instructors, enriching teaching materials, more flexible scheduling, and ongoing evaluation to optimize the program's impact. This research contributes to the development of an adaptive and comprehensive evaluation of religious programs based on the CIPP model.